(3GdTLQI TQM GdKeQI (B( (3aj Yde CMcGe GdfLhe (B)s - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3HWdejhS GdMcjes
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf hHYO , jbhd ehdGfG GdeYXe eMeO Hf eMeO GdWhSi Efg HMce ETGQI GdeNOhe PNQ GdhRQGA eMeO Hf eMeO GdLhjfi , dTQM cJGH KeQI HWdjehS s
(3BNQgG (B:s
(3hEf de jSQ aEf GdNGQLi ef MXjQI GdEbdje , jYfi ef hSW GdEbdje agPg JeGe cdeGJ cJGH GdKeQI hJaSjQgG hbO Je HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HChd GdeLehYI Jedc HGSe CMeO Hf CMeO Hf JeQJGT GdMfai SfI (B904(3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdadcs